Domesticating youth: youth bulges and their socio-political implications in Tajikistan - Roche, Sophie (Integration and conflict studies, 2014)
Placing the field sites in their context : a demographic history -- Why didn't you take a side? : the emergence of youth categories, institutions and groups -- Siblings are as different as the five fingers of a hand? : developmental cycle of domestic groups and siblingship -- The gift of youth? : workers, religious actors and migrants -- The only thing in life that makes you feel like a king? : marriage as an indicator of social and demographic changes -- Youth are our future? : the state's youth categories challenged by youth -- The dynamics of youth bulge as a question of domestication
Includes bibliographical references
Keywords: Hochschulschrift; Bürgerkrieg; Demographie; Soziale Situation; Soziologie; Jugend; Zentralasien; Tadschikistan